2015
DOI: 10.1016/j.jneuroim.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of inflammation and preservation of neurological function by anti-CD52 therapy in murine experimental autoimmune encephalomyelitis

Abstract: Alemtuzumab, a monoclonal antibody directed against human CD52, is used in the treatment of MS. To characterize the impact of anti-CD52 administration, a monoclonal antibody to mouse CD52 (anti-muCD52) was generated and evaluated in EAE mouse models of MS. A single course of anti-muCD52 provided a therapeutic benefit accompanied by a reduction in the frequency of autoreactive T lymphocytes and production of pro-inflammatory cytokines. Examination of the CNS revealed a decrease in infiltrating lymphocytes, demy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 25 publications
9
38
2
Order By: Relevance
“…In this study mCD52‐depleting mAb also depleted T cells and inhibited the development of relapsing EAE, which is associated with reduced immune infiltration and consequent reduced demyelination and neuroprotection . The depletion profiles appeared relatively similar to that seen in hCD52 transgenic CD‐1 mice injected with alemtuzumab and SJL and C57BL/6 mice injected with the mCD52‐depleting mAb .…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In this study mCD52‐depleting mAb also depleted T cells and inhibited the development of relapsing EAE, which is associated with reduced immune infiltration and consequent reduced demyelination and neuroprotection . The depletion profiles appeared relatively similar to that seen in hCD52 transgenic CD‐1 mice injected with alemtuzumab and SJL and C57BL/6 mice injected with the mCD52‐depleting mAb .…”
Section: Discussionsupporting
confidence: 61%
“…a,b). As alemtuzumab is administered as a set of five daily infusions in humans, five daily subcutaneous injections of mouse CD52‐mouse IgG2a mAb were administered according to instructions from the manufacturers. It was found that the relative percentages of both CD4 and CD8 T cells were now depleted by approximately 80–90% within 7 days of antibody delivery and this level of depletion persisted during an observation period of 28 days (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of anti-muCD52 not only reduces the number of circulating T lymphocytes, but also reduces the number of infiltrating T lymphocytes in the CNS of EAE mice, decreases the number of MOGreactive CD4 T cells and overall cytokine production and strongly inhibited the development of CNS inflammation and concomitant demyelination and axonal damage. Electrophysiological assessment showed preservation of axonal conductance in the spinal cord suggesting that anti-CD52 therapy may help to preserve CNS integrity [41]. Taken all together, these results demonstrate the robust general and local immunosuppressive action of anti-muCD52 treatment in several models of EAE and parallel the long term control of disease observed in the majority of RRMS patients treated with alemtuzumab.…”
Section: Experimental Autoimmune Encephalomyelitissupporting
confidence: 54%
“…These models have proven useful in developing and understanding currently approved DMTs including natalizumab (10), fingolimod (25), dimethylfumarate (24) or alemtuzumab (129). These models have proven useful in developing and understanding currently approved DMTs including natalizumab (10), fingolimod (25), dimethylfumarate (24) or alemtuzumab (129).…”
Section: Experimental Autoimmune Encephalomyelitismentioning
confidence: 99%